Development of Web-Based Digital Interactive Multimedia Using Google Sites to Improve Problem Solving Skills in Tax Administration Subjects at SMK N 6 Surakarta - Nisa, Siti Khoirun; Susilob, Agus (Jurnal Dakwah dan Komunikasi, 2025)
This research aims to develop web-based learning media using Google Sites as a learning solution for Tax Administration subjects at SMK N 6 Surakarta. The development was conducted using the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. In the analysis stage, it was found that conventional learning methods were less effective in improving students' understanding of tax concepts. Web-based media was designed with interactive features, such as learning videos, practice questions, and interactive games, developed using Google Sites. Expert validation results showed that this learning media has a very good level of feasibility, with an average validation percentage of 85% from material experts and 78.33% from media experts. Implementation was carried out through a limited trial involving grade XI students, showing a significant increase in learning outcomes with an average pretest score of 84 and posttest of 93. The final evaluation confirmed the effectiveness of the media in increasing students' learning motivation and understanding. This web-based learning media provides an innovative solution that supports a more interactive, flexible, and interesting learning process, and is able to create a more meaningful learning experience for students.